HLA class II associations with HIV-1 control in a black South African population - Murray, Lyle W (My University, 2020)
HLA class I alleles such as HLA-B*27 and HLA-B*57 have reliably been shown to associate with differential rates of HIV-1 disease progression. Little is known, however, of the association of HLA class II molecules and HIV-1 control. The increasingly important role that has been demonstrated for CD4+ T cells in HIV-1 pathogenesis suggests that HLA class II molecules may indeed play a significant role in HIV-1 control. We hypothesized that certain HLA class II alleles would be found at different frequencies in individuals who spontaneously control HIV-1 viraemia in the absence of antiretroviral therapy (Controllers) and in individuals with progressive disease (Progressors). We therefore determined HLA class II DPB1, -DQB1 and -DRB1 allele frequencies using sequence-based typing in a group of 26 black African Controllers and compared them to the allele frequencies that had previously been determined in 74 black African Progressors recruited from the same community in Johannesburg. The HLA class II alleles -DQB1*03:02:01 (P= 0.011, OR 0.16, CI 0.04 – 0.66) and - DRB1*04:01:01 (P=0.041, OR 0.16, CI 0.03 – 0.93) were found at significantly higher frequencies amongst Controllers than Progressors. In addition, the two-locus HLA class II haplotypes -DPB1*01:01:01/-DQB1*04:02:01 (P=0.015, OR 0.22, CI 0.07 – 0.74) and - DPB1*01:01:01/-DQB1*06:02:01 (P=0.029, OR 0.19, CI 0.05 – 0.85) were more frequent amongst Controllers than Progressors. These particular allele associations with HIV-1 control have not been shown before. These alleles may play a “protective” role in HIV-1 pathogenesis in black Africans. Our findings suggest an important role for HLA class II molecules and CD4+ T cells in HIV-1 control, however, due to the small number of participants in this study these findings highlight the need for better powered and more comprehensive studies on the role of HLA class II molecules on HIV-1 pathogenesis.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020